OVERALL CONTROL DALAM KONFLIK RUSIA DAN UKRAINA DALAM HUKUM HUMANITER: OVERALL CONTROL IN THE CONFLICT OF RUSSIA AND UKRAINE IN HUMANITARIAN LAW - Anabella, Angela June; Permanasari, Arlina (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2023)
The annexation of Crimea and the emergence of armed conflict between Russia and Ukraine has risen a question of the form of armed conflict itself. Despite Russia disputing any proof of aiding rebel forces, there are several clear indications of Russia’s influence over the separatist groups. Overall control plays an important role in determining the shape of the conflict, whether it has turned into an International Armed Conflict or remained a Non-International Armed Conflict. This Overall Control is encompassed in many international law, each with its unique definitions and thresholds, causing tensions in-between. It must be defined clearly which test should be applied in the dispute for the non-International Armed Conflict to turn into an International Armed Conflict. The overall control test is more likely to be met and reliable, providing superior protection under Humanitarian Law. The clear indication of planning and coordination done by Russia towards the separatist group’s military actions has then fulfilled the test of overall control that was ruled by the International Criminal Court of the Former Yugoslavia.